Development of a process for generating three-dimensional microbial patterns amenable for engineering use. Issue 27 (26th February 2016) - Mehta, Sunita; Murugeson, Saravanan; Prakash, Balaji; Deepak,
Abstract : We describe in detail a process for generating three-dimensional patterns of microbes on an optimum substrate in such a way that the patterns are amenable for engineering applications. Abstract : We describe in detail a process for generating three-dimensional patterns of microbes on an optimum substrate in such a way that the patterns are amenable for engineering applications. Further, we demonstrate approaches that make it possible to use the three-dimensional microbial patterns for applications outside the realm of the life sciences. Specifically, the microbes are normally grown on a gel media. In order to separate the grown patterns from the gel, we have introduced a permeable membrane. These membranes provide support for the growth of microbial colonies and allow them to be used in other applications. Among the membranes, a polyvinylidene fluoride membrane could be made suitable after its surface treatment to promote microbe adherence. We demonstrate two approaches for generating the required patterns. In both cases, a two dimensional pattern of an ink is dispensed on the membrane kept on the media. The subsequent growth of microbes is used to acquire the three dimensional pattern. The two proposed approaches are a microbial approach and an antimicrobial approach. In the former, baker's yeast, which was found to be the most suitable among the microbes tested, is dispensed in an ink form on selected locations on a PVDF membrane. The same pattern evolves upon growth. In the antimicrobial approach, the PVDF membrane is fully coated with yeast ink and iso-amyl alcohol as growth inhibitor is dispensed in a pattern. After growth of the yeast, the pattern evolved is the negative of the dispensed pattern. The fabricated patterns are proposed to be used in applications such as stamps for printing micro-electronics, microlenses, microfluidics and for direct use in braille printing. A polydimethyl siloxane stamp fabricated using a grown yeast pattern for micro-contact printing is also demonstrated.